Surgical closure of oroantral communication with L-PRF: a case report (Research, Society and Development, 2020)
Introduction: Pathological communication between the oral cavity and the maxillary sinus is a frequent sequela of traumatic events in the posterior region of the maxilla. Platelet concentrates, such as L-PRF, have been used in several clinical applications, including the management of extensive bucco-sinus communications. Objective: The present case report aims to describe the surgical closure of a sinus buccal communication using L-PRF associated with a vestibular flap. Case report: Female patient, melanoderma, smoker, with a history of chronic sinusitis associated with halitosis and secretion in the oral cavity for approximately three years, with onset of symptoms after maxillary molar extraction. Tomographic examination showed a bone defect measuring about 7 mm, communicating the oral cavity with the right maxillary sinus. Under local anesthesia, excision and debridement of the fistulous path was performed. The bone defect was filled with L-PRF membranes fixed below the periosteum and, then, the vestibular flap was advanced and placed in position for the complete closure of the bucco-sinusal communication. Following a 6-month postoperative follow-up, the patient did not show clinical or radiographic signs of maxillary sinusitis and computed tomography showed closure of bucco-sinusal communication. Conclusion: The use of L-PRF in the management of bucco-sinus communications can be considered an alternative to other techniques, with adequate repair of soft parts and important osteoinductive potential.